Odpowiedź :
Odpowiedź:
a) - 3x = 2x-10
-3x-2x= - 10
-5x= - 10 /*(-1)
5x= 10 /:5
x=2
b) 2x-2 = 7-x
2x+x= 7 +2
3x= 9 /:3
x=3
c) 10= 4-2x
10-4 = - 2x
6= - 2x /*(-1)
-6= 2x
-6 :2=x
-3=x
d) 5x-5 = 16 -2x
5x+2x= 16 +5
7x= 21 /:7
x= 3
Szczegółowe wyjaśnienie:
Odpowiedź:
a) -3x = 2x - 10
-3x - 2x = -10
-5x = -10 /: (-5)
x = 2
b) 2x - 2 = 7 - x
2x + x = 7 + 2
3x = 9 /: 3
x = 3
c) 10 = 4 - 2x
2x = 4 - 10
2x = -6 /: 2
x = -3
d) 5x - 5 = 16 - 2x
5x + 2x = 16 + 5
7x = 21 /: 7
x = 3
Liczę na naj ;))
Szczegółowe wyjaśnienie: